Restauraciones protésicas sobre implantes - Jorge Alberto Arismendi-Echavarria (Universidad de Antioquia, 1998)
Implant-supported restoration is an additional choice in Restoratile DentiStry. .4 Multi-professional team can offer adequate solutions to the patient. The lack of a structure like-ligament implies very special considerations about hiomechanics when you work implant-supported restorations. The main one is to avoid occlusal overload but a clear understanding of what constitutes occlusal overload is not available and, given all of the parameters in volved, likely, never will he. Then, the clinical judgment is the choice. The amount of prosthetic abutments in the market permit us to make aesthetic and functional restorations, including single tooth restorations, partially edentulous and complete edentulous restorations, with different techniques (both screw-retained or cemented restorations) and different materials like acrylic or porcelain teeth according with the patient needs.